2015
DOI: 10.4028/www.scientific.net/aef.13.194
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Water Quality in the Lakes Along Colentina River

Abstract: The purpose of this study is to evaluate the water quality in the lakes along Colentina River according to Romanian regulations referring to the norms on surface water quality classification, MO 161/2006. To achieve this goal, two sampling sections (entry and exit points) for each lake have been established, and the following indicators have been determined: pH, water temperature, dissolved oxygen, biochemical oxygen demand, chemical oxygen demand, nitrites, nitrates and ammonium nitrogen, total nitrogen, orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The level of phosphate phosphorus of 1.37 mg/L and nitrate nitrogen of 1.47 m/L produced a high density of euglenophytes, as reported by Rahman and Khan [30]. High phosphate levels were reported by other authors for Herastrau and Pantelimon lakes [23]. Concerning the influence of phosphorus on fish life, Jespersen and co-workers [31] showed that the bodyweight of cyprinids decreases with the increase in phosphorus content of water samples.…”
Section: Phosphorus Contentmentioning
confidence: 54%
See 2 more Smart Citations
“…The level of phosphate phosphorus of 1.37 mg/L and nitrate nitrogen of 1.47 m/L produced a high density of euglenophytes, as reported by Rahman and Khan [30]. High phosphate levels were reported by other authors for Herastrau and Pantelimon lakes [23]. Concerning the influence of phosphorus on fish life, Jespersen and co-workers [31] showed that the bodyweight of cyprinids decreases with the increase in phosphorus content of water samples.…”
Section: Phosphorus Contentmentioning
confidence: 54%
“…For investigated locations, the COD values (Table 4) are between 5 and 10 mg O2/L, this range allowing framing the analyzed waters into second quality class for surface waters. For Herastrau and Pantelimon lakes, other authors [23] reported COD values that allow framing the water from these locations in quality class II, as well. Results concerning nitrogen pollutant species In lakes, nitrogen appears as nitrite, nitrate, and ammonium ions, may come from fertilizers (synthetic or organic), wastes from septic systems, surface runoff, or groundwater sources, and all these forms may be used by aquatic plants and algae.…”
Section: Chemical Oxygen Demand (Cod) Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water indicators were analysed using adequate standardised methods and validated similar to procedures described elsewhere [38,39].…”
mentioning
confidence: 99%